Bipolar TURP decreases post-operative morbidity – A prospective study in a tertiary care hospital from north India - Maurya, Rajesh Kumar; Kumar, Vinay; Vineet, Kumar (Asian Journal of Medical Sciences, 2021)
Background: Transurethral resection of prostate is considered as gold standard surgical procedure for treatment of benign enlargement of prostate. It can be performed in two forms- monopolar transurethral resection and bipolar transurethral resection. Aims and Objective: This study was conducted to know which energy source among monopolar and bipolar energy leads to more post-operative morbidity after performing transurethral resection of prostate. Materials and Methods: In this study, total eighty (80) cases were included. They were suffering from lower urinary tract symptoms which were diagnosed to be due to benign enlargement of prostate after careful clinical and radiological examination. In forty cases, transurethral resection of prostate was performed by using monopolar energy source and in another forty cases, resection of prostate by transurethral route was done using bipolar energy source. Results: In our study, we found that development of TURP syndrome was more in monopolar TURP group in which pre-operative weight of prostate was more than 50 grams in comparison to bipolar TURP group in which there was no incidence of development of TURP syndrome in same class. Further, post-operative hospital stay and post-operative urethral catheter in situ was less in bipolar TURP group in terms of days as compared to monopolar TURP group. Conclusion: Our study concludes that Bipolar TURP is better in terms of development of less post-operative morbidity as compared to monopolar TURP. Bipolar TURP must be used extensively in teaching hospitals where students take more time than a seasoned surgeon to perform a surgical procedure and bipolar TURP will come handy in that situation.